Adding quality to the quilt : adolescent experiences of critical incident responses in secondary schools in Aotearoa New Zealand : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Social Work at Massey University (Palmerston North campus), New Zealand - Stewart, Kathryn Janet (Massey University, 2008)
Critical incidents impact on populations that experience them. Within secondary schools in Aotearoa New Zealand, there is an expectation that a response is made to schools that experience such incidents. There is much conflicting international research as to the efficacy of these responses. The adult experts are making decisions that they believe are in the best possible interests of the young people; they are putting together a quilt that they believe will nurture young people. The expertise and knowledge of a major stakeholder – the young people involved in the critical incident response – has been for the most part, omitted from research. This particular study set out to gather data about young people’s experiences of critical incident responses, so that the quilt being provided has input from this group and so is able to better meet their needs. The study had four major facets. It incorporated reflections on my intrinsic involvement in this field of practice and was, therefore, heuristic. Secondly, qualitative research was utilised to explore with young people their stories about what happened for them at the time of an incident. Thirdly, it incorporated principles of participatory research as an acknowledgement that young people are central stakeholders in secondary schools and that their voice was one that needed to be heard in order that the best responses may be offered. Lastly, it was utilisation focused. It was designed so that the findings were not just written up and filed away but disseminated to those who make decisions at the school level and policy level. At the analysis stage, two major methods were used. Firstly, inductive analysis was used to identify the themes that emerged from the interviews with the young people. Triangulation was then used to consolidate these themes using the input from Collaborative Groups and a systematic review of the knowledge that I have gained over the time that I have been involved with young people in the critical incident response area. This analysis of the contribution from the young people resulted in several areas being highlighted. Firstly, participants asked that those responding to critical incidents considered the use of language and the power of words, Secondly, they believed that schools needed to act proactively and to have a plan and, in association with this, that they develop a culture that better cared for the needs of young people. Thirdly, the young people involved requested that the ‘right’ people responded at the time of an incident: the qualities of the ‘right’ people and the ‘wrong’ people were also identified. Next, the young people were well able to identify the positives that could ensue out of negative situations, and lastly, they expressed their wish that there be a place for their involvement at the time of a critical incident response.
Keywords: Critical incident responses; Secondary schools; Adolescents; New Zealand; Participatory research; School crisis management; Crisis intervention; High school students; Fields of Research::330000 Education::330100 Education Studies::330199 Education studies not elsewhere classified